The The Effect Of Internal Control, Integrity, Information Asymmetricity On The Tendency Of Accounting Fraud - Viana, Yolanda Kerla; Rahayu, Sri; Herawaty, Netty (Jurnal Cakrawala Akuntansi, 2023)
This study aims to examine the influence of internal control variables, integrity and information asymmetry on the tendency of accounting fraud in the Regional Apparatus Organization (OPD) of the Jambi Provincial Service. This study uses a purposive sampling technique. The sample of this study was the head of the service, secretary and head of the finance and asset section of each OPD of the Jambi Provincial Service. Data collection was carried out by distributing questionnaires to 54 respondents, and only 41 questionnaires could be used. Data processing used SPSS 22.0 software. The results of the instrument quality test consisting of validity and reliability tests showed that all question items were valid and reliable. The results of the hypothesis test showed that simultaneously the performance measurement system, Integrity and Information Asymmetry influenced the Tendency of Accounting Fraud, while the Internal Control variable did not influence the Tendency of Accounting Fraud.